Modern challenges to the nonproliferaton regime and nuclear power from global initiatives; Методология проектирования молодежного научно-инновационного пространства для российской энергетики - Kondratjev D. O. (Nuclear technologies as integral part of engineering sciencein the modern world, 2013)
Заглавие с экрана